Peningkatan Hasil Belajar Servis Bawah Bolavoli Melalui Media Pembelajaran Audio Visual - Nur Amila; Khalid Rijaluddin; Maria Herlinda Dos Santos; Nia Febrianti (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2023)
This research aims to describe improvement in learning outcomes volleyball bottom serves through audio visual learning media at SMA 30 Bone and to prove the increase in learning outcomes volleyball bottom serves through audio visual learning media SMA 30 Bone. The research used classroom action research with a quantitative approach. The results showed, 10 students got scores high category, 7 people got scores medium category and 13 other people got low category. Overall, 20 students had not yet completed with a percentage 66.67% and 10 students had completed with a completion percentage 33.33%. In cycle there were 2 students who obtained grades in the very high category, 17 students high category, 7 students medium and 4 students low category. Overall there were 11 students who had not completed with a percentage of 36.67% and 19 students had completed with a completion percentage of 63.33%. Meanwhile, at the end of cycle II there was an increase in the quality of learning to serve under the game of volleyball where there students who completed it with a percentage 100%. The conclusion of the research shows through audio visual learning volleyball can improve student learning outcomes at SMA 30 Bone.